Cloud Service for Analysis and Interactive Visualization of Weather Data in Armenia - Grigoryan, Hayk A.; Abrahamyan, Rita M. (Mathematical Problems of Computer Science, 2021)
The Lesser Caucasus Mountains are crossing through the territory of Armenia, creating vast differences in altitude, terrain, temperature and precipitation in provinces and towns. Even Armenia’s lowlands are 500 to 1500m above sea level. Armenias highlands extend up to Aragats mountain at 4090m where, 75% of the territory is above 1000m, 50% is above 2000m, and 3.4% is above 3000m. This paper presents a cloud service with interactive visualization and analytical capabilities for weather data in Armenia by integrating the two existing infrastructures for observational data and numerical weather prediction. The weather data used in the platform consist of near-surface atmospheric elements including air temperature, relative humidity, pressure, wind and precipitation. The visualization and analitycs have been implemented for 2m air temperature. Cloud service provides the Armenian State Hydrometeorological and Monitoring Service with analytical capabilities to make a comparative analysis between the observation data and the results of a numerical weather prediction model for per station and region for a given period.